Speciation reversal in sympatric eco-morphs of European whitefish (Coregonus lavaretus. L) – phenotypic and genomic consequences - Bhat, Shripathi (UiT The Arctic University of Norway, 2016)
The papers II and III of this thesis are not available in Munin. Paper II : Bhat, S., Bernatchez, L., Amundsen, P. –A., Fevolden, S. –E., Benestan, L., Præbel, K.: «Speciation reversal leads to unpredictable genomic outcomes in European whitefish”. (Manuscript). Paper III: Bhat, S., Lamaze, F. C., Bernatchez, L., Præbel, K.: “Effect of speciation reversal on genomic introgression in sympatric whitefish eco-morphs.” (Manuscript). Anthropogenic activities, such as introduction of non-native species, is considered as one of the most significant causes for declining biodiversity, since such introduction may destabilise ecological barriers to gene flow between native populations. In the 1960s a salmonid fish, vendace, was introduced to the upper parts of Pasvik watercourse and during the early 1990s it invaded the entire watercourse, including the lakes studied in this project/thesis. These lakes harbour an eco-morph pair of European whitefish that has diverged in sympatry in post-glacial times. The vendace, being a competitively superior planktivore to the densely rakered eco-morph, relegated this eco-morph from its native pelagic habitat into the non-native littoral habitat, which is mainly occupied by the large sparsely rakered eco-morph. These observations have inspired this PhD thesis to study the phenotypic, genetic, and genomic consequences of the vendace invasion on native sympatric European whitefish eco-morphs. Using neutral microsatellite markers, the study documented that the introduction and invasion of vendace have induced speciation reversal in the eco-morph pair. The comparison of the number of gill rakers from the pre- and post-invasion periods revealed merging of two peaks of distribution of number of gill rakers following the invasion suggesting reduction in discreteness of phenotypes. Population genomic analyses, using genome-wide coverage of SNP markers obtained by sequencing of restriction site associated DNA libraries (RADseq), revealed an unpredicted outcome of speciation reversal at the ...